1995
DOI: 10.1295/polymj.27.1113
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Structure of Cuprammonium Cellulose I. A Circular Dichroism Study on the Dissolved State of Cellulose in Cuprammonium Solution

Abstract: ABSTRACT:An attempt was made to clarify the dissolved state of cellulose in aq cuprammonium hydroxide solution using ultraviolet (UV) and circular dichroism (CD) spectrophotometry on cellulose and its oligomers in the solution. Negative Cotton effect and positive Cotton effect for the cellulose--cuprammonium solution are observed at 300--350 nm and ca. 600 nm. The former Cotton effect seems to originate from charge transfer (CT) excitation and the latter from d--d excitation of cupric ion due to coordination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Today, commercial production is either carried out via the viscose (Huber et al 2011;Klemm et al 2004) or the Lyocell processes (Rosenau et al 2002), using derivatizing and non-derivatizing solvents, respectively; these processes involve toxic derivatization steps or toxic and expensive chemicals. There are other known routes for cellulose dissolution with inorganic complexes (Miyamoto et al 1995;Saalwächter et al 2000), or certain exotic organic solvents (Philipp 1993), which, however, cannot be considered sustainable for large scale production. In the early 1990s, alkali-based aqueous solvents started to gain more academic and technical attention for the reasons of being more environmental benign than other protocols (Isogai and Atalla 1998;Kamide et al 1992;Zhou and Zhang 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Today, commercial production is either carried out via the viscose (Huber et al 2011;Klemm et al 2004) or the Lyocell processes (Rosenau et al 2002), using derivatizing and non-derivatizing solvents, respectively; these processes involve toxic derivatization steps or toxic and expensive chemicals. There are other known routes for cellulose dissolution with inorganic complexes (Miyamoto et al 1995;Saalwächter et al 2000), or certain exotic organic solvents (Philipp 1993), which, however, cannot be considered sustainable for large scale production. In the early 1990s, alkali-based aqueous solvents started to gain more academic and technical attention for the reasons of being more environmental benign than other protocols (Isogai and Atalla 1998;Kamide et al 1992;Zhou and Zhang 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, authors have confirmed that cellulose exists as b chelate structure with coordination of cuprammonium ions to hydroxyl groups at c2 and c3 positions of glucopyranose unit in cuprammonium hydroxide solution. 7 In addition, authors also revealed that the similar cellulosejcuprammonium hydroxide complex as that in solution could exist even in a solid state. 8 This means that the change in the chelate or complex structure of cellulose during coagulation process must be considered to discuss the morphological formation of the membrane besides simple phase equilibrium study.…”
mentioning
confidence: 99%
“…11 • 12 Some voids are seen especially for D series membranes. In any cases, the surface of D series membranes except for DCe 9 Ca 1 have far smaller pore than those for W series. The net work structure in which polymer particles are mutually connected to form pores are obvious especially for the surface of W series membranes.…”
Section: Resultsmentioning
confidence: 78%
“…Cotton linter supplied by Peterdemings Co., Ltd., was dissolved in aq cuprammonium hydroxide solution according to the known procedure 9 at cellulose concentration of 8 wt%. The molar composition of the solution (cellulosejCujNH 3 ) was adjusted constant as 0.05/ 0.046/0.36.…”
Section: Cellulose Solution Casein Solution and Their Mixturesmentioning
confidence: 99%
See 1 more Smart Citation